HESS Management for Virtual Inertia, Frequency, and Voltage Support Through Off-Board EV Bidirectional Chargers - Paucara, Jhonatan D. (2024)
The massive integration of renewable energies into the grid using fast-response converters without inertia generates issues such as inertia reduction, temporary voltage violations, and power quality reduction. The system inertia reduction is a critical problem that could lead to grid frequency exceeding the acceptable range, resulting in undesirable load-shedding or even large-scale blackouts. To overcome these issues, the use of electric vehicle bidirectional chargers (EVBCs) implementing functionalities such as distributed virtual inertia (VI), long-term frequency support, voltage support by reactive power, and harmonics compensation, has been proposed as a possible solution. This article proposes a novel control strategy to manage a hybrid energy storage system (HESS) composed of dc-link capacitors and battery, through an isolated two-stage ac–dc converter (composed of a dual active bridge resonant type dc–dc converter cascaded to a voltage source inverter), intended for off-board EVBCs. The HESS management allows decoupling of the active power dynamic response since dc-link capacitors supply the fast dynamic response for VI support whereas the battery supplies the slower dynamic response for long-term frequency support, respectively. Hence, the VI support does not affect the battery lifetime. Simulations and experimental results are presented for a 2.5 kW prototype to validate VI, frequency-voltage support along with harmonics compensation.